Use of Dexmedetomidine for Preventing Pain on Propofol Injection: A Double Blinded Placebo Controlled Study - Hossain, Muhammad Sazzad; Rahman, Md Afzalur; Alamgir, Md Mahiuddin; Md Waliullah, -; Sarker, Paresh Chandra; Islam, Nadia; Islam, Md Sirajul (Anwer Khan Modern Medical College Journal, 2019)
Background and aim of study: Propofol is a commonly used drug for general anesthesia. It can irritate the skin, mucous membrane and venous intima. The main drawback is the pain during intravenous injection. Aim of this prospective randomized study is to observe the efficacy of intravenous dexmedetomidine as pretreatment for the prevention of pain caused by the propofol injection. Methods: A total of 80 adult patients were selected in this study with either sex, ASA (American Society of Anesthesiologists) grade I and II, scheduled for routine elective surgical procedure under general anesthesia. The patients enrolled were divided randomly into two groups of 40 patients each. Group received 0.25 mcg of intravenous dexmedetomidine in 5 ml. Group II (placebo group) received 5 ml of 0.9% intravenous normal saline one minute before injection of propofol. The patients were asked to report their pain during injection of propofol according to the McCririck and Hunter scale. Results: The incidence of pain experienced in dexmedetomidine group was 35% patients and in saline group was 70% patients (p<0.05). The severity of POPI was also lower in dexmedetomidine group than the saline group (p<0.05). The incidence of mild and moderate pain in dexmedetomidine groups versus saline group was 20% versus 45% and 15% versus 25% respectively p<0.05. There was no severe pain recorded in any groups. Conclusion: Pretreatment with 0.25 mcg/kg of dexmedetomidine with venous occlusion for one minute, effectively reduces pain on propofol injection. Anwer Khan Modern Medical College Journal Vol. 10, No. 2: July 2019, P 164-168